2016
DOI: 10.5114/jcb.2016.64919
|View full text |Cite
|
Sign up to set email alerts
|

Whole breast irradiation vs. APBI using multicatheter brachytherapy in early breast cancer – simulation of treatment costs based on phase 3 trial data

Abstract: PurposeA recent large phase 3 trial demonstrated that the efficacy of accelerated partial-breast irradiation (APBI) in the treatment of early breast cancer is non-inferior to that of whole breast irradiation (WBI) commonly used in this indication. The aim of this study was to compare the costs of treatment with APBI and WBI in a population of patients after conserving surgery for early breast cancer, and to verify if the use of APBI can result in direct savings of a public payer.Material and methodsThe hereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, a cost-effectiveness analysis comparing APBI in a single fraction versus WBI or even APBI in several fractions could be performed. In fact, in a cost-effectiveness analysis of Harat et al ., a greater cost-effectiveness was found for APBI [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a cost-effectiveness analysis comparing APBI in a single fraction versus WBI or even APBI in several fractions could be performed. In fact, in a cost-effectiveness analysis of Harat et al ., a greater cost-effectiveness was found for APBI [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cost effectiveness of MIB-APBI technique was shown in a study by Harat et al . [ 2 ]. This study has analyzed average cost of treatment and incremental cost-effectiveness ratio of MIB-APBI compared to WBI in early breast cancer patients over a 5-year period, based on the results of GEC-ESTRO trial.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year local control, disease-free survival, and overall survival were similar in the two arms, along with lesser rate of late normal tissue toxicity with APBI [ 1 ]. Cost simulation based on the result of this study has shown that APBI is a cost-effective alternative to WBI [ 2 ]. Satisfaction with the cosmetic outcome and quality of life scores are also higher with MIB-APBI compared to WBI [ 3 ].…”
Section: Purposementioning
confidence: 99%
“…Currently, interstitial and intracavitary BT in breast cancer is used in the context of APBI after lumpectomy for a highly select group of patients as an alternative to whole breast irradiation (WBI). Despite randomized trials demonstrating equivalent local control, 112,113 less time investment for the patient, and lower cost, 114 APBI BT is not as commonly used as WBI. Reasons include the technical skill and training required on the part of the physician but also patient exclusion because of the anatomic location of the lumpectomy cavity, leading to the inability to meet dose constraints for OARs.…”
Section: Breast Cancermentioning
confidence: 99%
“…The literature for conventional HDR-BT reports fairly low rates of chest wall pain and rib fractures (w21.3% and 1.8%, respectively), likely as a result of these guidelines. [112][113][114][115][117][118][119] The reduced dose to these structures with IMBT suggests the possibility of reducing these margins and therefore increasing the patient population for whom APBI may be a viable option.…”
Section: Breast Cancermentioning
confidence: 99%